Factors affecting risk level of work postures of durian farmers during pesticide spraying in southern peninsular Thailand: A cross-sectional study (International Journal of Occupational Safety and Health, 2026)
Introduction: Work-related musculoskeletal disorders (WMSDs) are a major occupational health problem among farmers in Thailand. The purpose of this study was to evaluate the risk level and risk factors in work posture of durian farmers during pesticide spraying.Methods: This cross-sectional study was carried out among 82 durian farmers (n = 82) in southern peninsular Thailand. A questionnaire was used to collect data on socio-demographics and work characteristics. The posture analysis during pesticide spraying was done using Rapid Entire Body Assessment (REBA). The Chi-squared test was applied to find associations between socio-demographics or work characteristics with the risk level according to REBA assessments, with statistical significance requiring p